The Predictive Indicators of The Contribution of Some Physical Abilities to The Quantitative Estimation Of The smash shot of Volleyball Players - lebchiri, ahmed (sports creativity, 2025)
This study aims to know predictive indicators of some physical abilities to the quantitative estimation of the smash shot, by deducing predictive indicators using multiple linear regression, which can contribute to building a database to determine quantitative values for skill abilities through prior mathematical equations8 In order to reach the results, the researcher used the descriptive approach , The researcher also used a set of physical and skill tests to reach the results. The study sample included 14 players from the Raed-Msila Volleyball Club (RCM). the study results were within the predictive equation according to the study variable ( Smash Skill) as follows= - The Predictive estimation for smash Skill (score) = 56.822 + (-0.401 × explosive power of legs cm) + (-0.765 × explosive power of arms cm) + (-1.674 × agility S) + (-18.707 × reaction speed S) + (-0.189 × neuromuscular coordination S).